Eksplorasi Kesejahteraan Psikologis pada Pasien Brachial Plexus Injury (BPI) - Ayu Febryanti, Yusrina; Untari, Rita (Jurnal Terapi Wicara dan Bahasa, 2023)
Background: Brachial plexus injury is an injury to the C1-T1 nerve that most commonly occurs in men of reproductive age. This injury can cause motor and mental disability because it requires more than one surgery with a long recovery time. However, existing rehabilitative services focus more on restoring motor skills or functional abilities and less on evaluating psychological conditions, coping and quality of life. Objectives:The purpose of this study is to determine how the condition of psychological well-being and how BPI patients manage or maintain their psychological well-being. Methods:The method used is qualitative with a phenomenological approach. The number of participants was 6 patients from Soeharso Orthopedic Hospital, Surakarta who were selected through purposive sampling technique. Data was collected by in-depth interviews, then analyzed by content analysis. Results:The results showed that all BPI respondents experienced changes in the dimensions of psychological well-being. Conclusions:The dimensions that have experienced the most changes are self-acceptance, positive relations with others, purpose in life and environmental mastery. In addition, respondents also felt a change in subjective well-being. Adaptive strategies and emotional focused coping are most often used by respondents to maintain psychological well-being and adapt to life changes. By exploring this aspect, it can be taken into consideration in determining intervention that supports patient's independence. Keywords: Psychological well-being, Quality of life, Brachialis Plexus Injury